أثر تطبيق منظومة الجدارات المهنية على تطوير قطاع التعليم الفندقي بالتطبيق على المدرسة الثانوية الفندقية بمطروح - هريدى، باسم محمود أبو العلا (جامعة الفيوم - كلية السياحة والفنادق, 2021)
يعد التعليم الفندقي واحدا من قطاعات التعليم الفني التي تسهم بنصيب وافر في إعداد القوى البشرية المدربة والقادرة على التعامل مع متطلبات السوق السياحي، وعلى الرغم من ذلك فقطاع التعليم الفندقي كان يعاني من أوجه قصور التي تؤثر على جودته وعدم مسايرته لمتطلبات السوق الحالية، لذا كان من الضروري تطوير مناهج التعليم الفندقي لتضييق الفجوة بين مستويات الخريجين وشروط العمل المتاحة بالسوق. وقد بدأ قطاع التعليم الفني والجدارات بوزارة التربية والتعليم بتطبيق نظام التعليم الفني المبني على منظومة الجدارات، من خلال تطوير شامل لكافة المناهج الدراسية بهدف إعداد كوادر بشرية مدربة قادرة على مواجهة تحديات ومتغيرات سوق العمل المحلي والدولي والإقليمي، وبداية من العام الدراسي 2019/ 2020 تم اختيار المدرسة الثانوية الفندقية بمطروح- نظام الثلاث سنوات ضمن (15) مدرسة فندقية على مستوى الجمهورية ليتم تطبيق منظومة الجدارات المهنية بها. وقد اعتمدت الدراسة على المنهج الوصفي بهدف وصف وتفسير الوضع على أرض الواقع وكذلك التعرف على الآثار المترتبة على تطبيق منظومة الجدارات المهنية على تطوير وإكساب المعارف والمهارات والمعلومات والسلوكيات اللازمة للطلاب لكي يؤدوا مهام وظائفهم بكفاءة بعد تخرجهم، وكذلك إلقاء الضوء على أثر تطبيق منظومة الجدارات المهنية على إعداد كوادر بشرية مدربة ومؤهلة، وقد توصلت الدراسة إلى بعض النتائج من أهمها انعكاس تطبيق منظومة الجدارات المهنية بالمدرسة الفندقية على سرعة انتقال الطلاب إلى سوق العمل، وأيضا توصلت الدراسة إلى العديد من التوصيات من أهمها ضرورة توفير عدد أكبر من المعلمين القائمين على تطبيق المنظومة وخاصة المتخصصين بالتعليم الفندقي."
Hotel education is a branch of the technical education that participates with a large share in preparing graduates of hotel education and it deals with requirements of the market However, the hotel education sector suffered from some of deficiencies that affected on its quality and it did not keep pace with the requirements of the current market, so it was necessary to develop hotel education curricula to narrow the gap between the levels of graduates and the conditions of work available in the market. It is in that spirit that the importance of hotel education, the technical education sector began, at the Ministry of Education, to apply the technical education system based on the competency system through extensive development of all school curricula aiming at preparing trained human stuff who are capable of facing challenges and changes of the local, international and regional labor market. Starting from the academic year 2019/ 2020, the Hotel Secondary School in Matrouh–a school of three-year system -has been chosen within the fifteen hotel schools through Egypt, in order to apply the professional competency system in. The study relied on the descriptive approach in order to describe and explain the situation on the ground, As well of the professional competency system on developing and acquiring knowledge, skills, information and behaviors which are necessary for students to perform their tasks efficiently after their graduation, As well as shedding light on the effect of applying the system of professional competencies on preparing trained and qualified human cadres, and the study reached some results, the most important of which is the reflection of the application of the professional competencies system in the hotel school on the speed of students ’transition to the labor market, and the study also reached many recommendations, the most important of which is the necessity to provide A larger number of teachers who implement the system, especially those who specialize in hotel education."
Keywords: الجدارات المهنية -- التعليم الفني -- التعليم الفندقي -- الثانوية الفندقية -- مطروح